Morphology of cracks and shear bands in polymer-supported thin film metallic glasses. (September 2021) - Glushko, Oleksandr; Gammer, Christoph; Weniger, Lisa-Marie; Sheng, Huaping; Mitterer, Christian; Eckert, Jürgen
Abstract: Here we provide a systematic study of tensile deformation mechanisms in PdSi metallic glasses employing polymer-supported sputter deposited films. Due to the polymer substrate, global strain localization within one critical shear band is inhibited and thus thousands of different shear bands and cracks can be examined within a single tensile sample. Two distinctly different types of shear bands, allowed by the sample geometry, are observed and analyzed. It is shown that crack formation occurs through activation of multiple out-of-plane shear bands leading to local plasticity and neck-like shape of crack edges. The in-plane shear bands, which appear at higher applied strains, typically do not lead to crack formation and can accommodate both applied tensile strain and transverse compressive strain. The mechanism of effective strain hardening through de-activation of in-plane shear bands is demonstrated by means of quasi-in-situ studies. Shear banding is shown to be the fundamental deformation mechanism for different film thicknesses ranging from 25 to 1000 nm. Polymer-supported films represent a unique model material system which enables easy characterization of the tensile behavior of metallic glasses and provides an opportunity to gain new insights into the fundamental mechanisms of shear banding. Graphical Abstract: ga1